ChemInform Abstract: Carboxylative Coupling Reaction of Five‐Membered (Chloromethyl)heteroarenes with Allyltributylstannane Catalyzed by Palladium Nanoparticles. Issue 12 (March 2016) - Sun, Jian; Bao, Ming; Feng, Xiujuan; Yu, Xiaoqiang; Yamamoto, Yoshinori; Almansour, Abdulrahman I.; Arumugam, Natarajan; Kumar, Raju Suresh
Abstract: The precatalyst Pd(acac)2 reacts with stannane (II) in the presence of the stabilizer Bu4 NBr to furnish palladium nanoparticles which catalyze the three‐component coupling to afford β, γ‐unsaturated esters.